Immobilization of Lactobacillus plantarum B134 Cells using Sodium Alginate for Lactose Hydrolysis in UHT Milk - Lusiana Kresnawati Hartono; Tatik Khusniati; I Made Artika; Sulistiani sulistiani; Abdul Choliq (IPB University, 2014)
Hydrolysis of lactose in milk by β-galactosidase from immobilized bacterial cells has the potential to alleviate the problem of lactose intolerance. The present study was aimed to immobilize cells of L. plantarum strain B134 and evaluate their efficiency in hydrolyzing lactose in ultra high temperature (UHT) milk. Immobilized cells were generated by mixing cell suspensions with solutions of sodium alginate and calcium chloride. The β-galactosidase activity of the immobilized cells was tested by determining their ability in hydrolyzing lactose in UHT milk (whole milk and skimmed milk). Results showed that cells of L. plantarum strain B134 were entrapped optimally using a combination of 1 % sodium alginate, 100 mM calcium chloride and 12 % w/v cell suspension. The highest β-galactosidase activity was achieved at pH 6.5 and a temperature of 45 ºC for 5 minutes incubation time. The immobilization efficiency achieved was 28.95 %. The immobilized cells could reduce lactose by up to 85.45 % in UHT whole milk and 91.26 % in UHT skimmed milk. The times required for that reduction of lactose in UHT whole milk and UHT skimmed milk were 12 hours and 9 hours respectively. The immobilized cells could be re-used up to 4 times for efficient lactose hydrolysis for both types of milk. Therefore, immobilized cells of L. plantarum B134 have the potential to be used for lactose hydrolysis in UHT milk.